ANALISIS JABATAN SEKTOR PUBLIK (STUDI KASUS BADAN PENDAPATAN DAERAH KOTA PEKANBARU) - Lubis, Fitri Afalda; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract                Analysis of the Position of the Regional Revenue Agency of the City of Pekanbaru is still a mismatch between the position and the field of science currently occupied. This means that the level of education in the field of science has not yet been fully taken into consideration. The purpose of this researcher is to find out information on the position analysis of the Regional Revenue Agency of the City of Pekanbaru. Information collected through job analysis plays an important role in human resource planning because it provides data on staffing conditions and the work environment. The indicators used are Permenpan RB Number 38 Year 2017, namely job requirements including rank, education qualification, type of training, measure of job performance and work experience. The research method used is qualitative with a type of case study approach with data collection techniques through interviews, observation and documentation. The selection of research informants using purposive sampling method. The results of this study indicate that the analysis of the position of the Pekanbaru City Revenue Agency is still not appropriate between positions and levels of education with the motto "The right man on the right place" which means placing the right person in the right place and the factors that hinder the analysis of the Board of Education office. The area of Pekanbaru City is human resources and proximity factors.   Keywords: Job Analysis, Job Specifications